Further Records of Ground beetles (Coleoptera: Carabidae) from Oman - Al-Jahdhami, Ali (2021)
The Carabidae family has a cosmopolitan distribution and form one of the most diverse and abundant group of insects. These beetles play an important role in ecosystems as bioindicators in habitat management, landscape ecology, conservation, pollution, climatic changes and soil characteristics. The knowledge of Carabidae from Oman is still not well studied. Only 44 species of Carabidae are reported from Oman so far and this indicates the large blank in our knowledge in this family when compared to recorded species from other neighboring countries in the Arabian Peninsula. A total of 37 specimens were collected, and 10 species from 10 genera and 4 subfamilies are being new records for Oman. The sampling was conducted by light traps and by hand.  All reported species were collected from northern Oman (Wadi Alkoudh- Oman botanical garden-, Samad Ashan and Wadi beni Khalid). The vegetation was rich with the Leguminosae, Asteraceae and Poaceae. Most species were collected during autumn from wadi habitat. The carabid fauna was dominated by the Lebiinae and Harpalinae with 8 species. The species belong to Lebiinae are four species (Tetragonoderus arcuatus Dejean, 1829, Microlestes discoidalis (Fairmaire, 1892), Metadromius ephippiatus (Fairmaire, 1884) , Singilis persicus (Jedlička, 1961)), four from Harpalinae (Crasodactylus punctatus Guérin-Ménéville, 1847, Amara maindroni Bedel, 1907, Amblystomus orpheus LaFerté-Sénectère, 1853, Zuphium olens P. Rossi), one species from Trechinae (Elaphropus babaulti (Andrewes, 1924)) and one from Scaritinae (Dyschirius schaumi (Putzeys,1866)).